Mechanical properties and fatigue behavior of CO2 laser beam welded armor steel joints - Balalan, Zulkuf; Sarsilmaz, Furkan; Ekinci, Omer (Walter de Gruyter Gmbh, 2020)
Armor 500T steel used in armored military vehicles and marine vehicles were joined by CO2 laser beam welding method by applying three welding powers and two welding speeds under shielding argon atmosphere. From microstructure and microhardness results, under low laser welding power and high welding traveling speeds, microstructural transformation in the joining region of the performed welds occurred at a narrower distance as compared to other parameters, and it was determined that four regions formed independent of each other for each parameter group. Furthermore, it was determined that there is a gradual decrease in the microharness values of samples in which welding parameters cause heat input to decrease. The fatigue test results of all samples showed high strength properties in the parameters with high heat input. Additionally, tensile test results for all samples with high heat input parameters also exhibited high strength properties. Fracture at the intersection at high heat input parameters of a relatively ductile separation type occurred in HAZ, whereas, at other parameters fracture occurred at the weld center and wide gap semi-brittle fracture behavior was observed. As a consequence, it was found that the most effective parameter as compared with laser welding power is laser welding traveling speed.
Keywords: Armour steel; mechanical properties; microstructure; laser welding; fatigue